Hybridization in the labor children's school curriculum: A multiperspective study - Hidayat, Panji; Widodo, Hendro; Nuraini, Febritesna (Universitas Ahmad Dahlan, 2024)
If education is not managed effectively, it will remain incomplete and produce suboptimal results. Additionally, the predominant workforce in Indonesian society often leads to less-than-optimal supervision of children, resulting in workplace anxiety and discomfort due to inadequate childcare. The discrepancy between school hours and parents' working hours often leads to neglect of children's studies. Consequently, the author is deeply motivated to elucidate the research objectives, which focus on identifying the model or format of curriculum hybridization suitable for children of workers and determining the necessary preparations for implementing such a hybrid curriculum at SD Muhammadiyah Warungboto Yogyakarta. This research aims to provide insights into appropriate curriculum hybridization and the requisite preparations for its implementation. The research methodology employed is qualitative descriptive, drawing upon several references related to curriculum hybridization. The findings underscore the crucial necessity of curriculum hybridization, particularly in fostering parental comfort with the educational system by integrating play theory and children's games into the school curriculum. SD Muhammadiyah Warungboto serves as a pivotal institution for developing and strengthening a curriculum tailored to the needs of children from working families. Preparatory measures encompass infrastructure enhancements, provision of playgrounds and gaming facilities, accommodation facilities, counseling services, teacher training initiatives, and the recruitment of instructors specializing in talent and the arts. In conclusion, the research highlights the significance of curriculum hybridization for children of working parents, given the prevalent 8-hour workday norm. The integration of the national curriculum with elements of play and games is paramount. Such integration demands comprehensive preparations, not only concerning infrastructure and teacher readiness but also in tailoring the curriculum to suit the unique needs and conditions of the children.